2021
DOI: 10.24115/s2446-6220202173d1702p.153-158
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of the readiness for self-improvement of the future teacher in the conditions of COVID-19

Abstract: The purpose of the article is to study a system for diagnosing a future teacher's readiness for self-improvement in the context of COVID-19. The high requirements of modern society for the personality, the level of professional competence and activities of educators, and as a result, new requirements for the training of pedagogical personnel and advanced training of teachers in the vocational education system imply the development of not only their professionally significant qualities, but the personality as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They concluded that acmeological conditions that contribute to the formation of lifestyle are shown. Kryshtanovych, Bilyk, Tkachov, Gontar, and Tkach (2021) aimed to examine a system to diagnose whether a future teacher is ready for self-development in the context of COVID-19, and as a result, the effectiveness value paradigm of modern education and the existence of the teacher's subjective position concerning his development are associated with acmeological currents. It is seen that they have reached their values of strengthening.…”
Section: Related Researchmentioning
confidence: 99%
“…They concluded that acmeological conditions that contribute to the formation of lifestyle are shown. Kryshtanovych, Bilyk, Tkachov, Gontar, and Tkach (2021) aimed to examine a system to diagnose whether a future teacher is ready for self-development in the context of COVID-19, and as a result, the effectiveness value paradigm of modern education and the existence of the teacher's subjective position concerning his development are associated with acmeological currents. It is seen that they have reached their values of strengthening.…”
Section: Related Researchmentioning
confidence: 99%